Penafsiran Zaghlul al-Najjār terhadap Atom Bertasbih dalam Kitab Tafsĭĭr al-Āyat al-Kauniyyah fĭ al-Qur’ān al-Karĭm - Muhammad Hilman Hirzi; Hakam Chozin, Fadjrul (IAIN Madura, 2024)
There are some mufasir who argue that tasbih is only done by living creatures. However, this opinion is not in accordance with the Qur'an surah Al-Isra' verse 44 which suggests that everything tasbih to Him. Zaghlul al-Najjār interpreted the Qur'an surah Al-Isra' verse 44 in his book Tafsĭr al-Āyat al-Kauniyyah fĭ al-Qur'ān al-Karĭm explaining that tasbih is carried out by objects live and die with a comprehensive discussion of science compared to other commentators. The focus of the problem is how to interpret Zaghlul al-Najjār's atomic beads and their relevance to modern science. This research will complement the discussion of previous research on atomic prayer beads. This research method applies descriptive analysis and content analysis which thoroughly explores the content that needs to be investigated in the entire text. In Zaghlul al-Najjār's interpretation of atomic prayer beads there are many similarities and few differences with contemporary scientific theory. This is an implication of Zaghlul al-Najjār, who is one of the contemporary scientific commentators.